## Solving the Equation: (x+2)^2 - 3 = 1

This article will walk through the steps involved in solving the equation **(x+2)^2 - 3 = 1**.

### Step 1: Isolate the Squared Term

**Add 3 to both sides of the equation:**(x+2)^2 - 3 + 3 = 1 + 3**Simplify:**(x+2)^2 = 4

### Step 2: Take the Square Root of Both Sides

**Apply the square root operation to both sides:**√[(x+2)^2] = ±√4**Simplify:**x + 2 = ±2

### Step 3: Solve for x

**Isolate x by subtracting 2 from both sides:**x + 2 - 2 = ±2 - 2**Simplify:**x = -2 ± 2

### Step 4: Calculate the Solutions

**Calculate the positive solution:**x = -2 + 2 = 0**Calculate the negative solution:**x = -2 - 2 = -4

### Conclusion

Therefore, the solutions to the equation (x+2)^2 - 3 = 1 are **x = 0** and **x = -4**.